Determining Factors of the Use of Medication Label: The Case of Malaysia - Cheah, Yong Kang (2016)
The use of medication label can help to lower the risk for misuse of medicine. The present study attempts to investigate the demographic, lifestyle and health determinants of the use of medication label among adults in Malaysia. A nationally representative data that consists of a large sample size is employed. The findings of the present study show that age, income, gender, education, ethnicity, marital status, house locality, employment status, physical activity, smoking, hypercholesterolemia and diabetes are significantly associated with the decisions of individuals to use medication label. In particular, age and unhealthy lifestyle reduce the likelihood of using medication label, whereas education level, being married and employed, and having chronic diseases increase the probability o f using. The present study suggests that intervention measures directed toward encouraging the use of medication label among the individuals who have a low tendency to use medication label may ensure desirable outcomes.